The contribution of FBOs working with the displaced - Holdcroft, D (Refugee Studies Centre, University of Oxford, 2014)
Faith-based organisations take from their religious traditions both strong motivations and access to a long history of thinking concerning social and political issues. This can make them ideally placed to fill the gaps in the implementation of human rights.